1983
DOI: 10.1136/bmj.286.6377.1539
|View full text |Cite
|
Sign up to set email alerts
|

Profile of recovery after general anaesthesia.

Abstract: The duration of impairment of mental functioning after anaesthesia was studied in 55 patients undergoing hernia repair who were divided into three groups in which the method of induction of anaesthesia (intravenous or inhalational) and ventilation (spontaneous or controlled) was varied. Performance in a five minute serial reaction time test and subjective estimates of coordination were assessed four times a day for two complete postoperative days and were compared with those in a control group of orthopaedic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(5 citation statements)
references
References 5 publications
1
3
0
1
Order By: Relevance
“…There was also evidence suggesting that learning of the task was impaired for up to 2 days after anaesthesia. The data are consistent with an earlier reaction time study in middle-aged patients, which used a similar control group of orthopaedic patients, and halothane anaesthesia, and in which performance was impaired for up to 48 h after anaesthesia [10]. However, only means of blocks of reaction time trials were reported, and it was not possible to compare our data directly.…”
Section: Discussionsupporting
confidence: 89%
“…There was also evidence suggesting that learning of the task was impaired for up to 2 days after anaesthesia. The data are consistent with an earlier reaction time study in middle-aged patients, which used a similar control group of orthopaedic patients, and halothane anaesthesia, and in which performance was impaired for up to 48 h after anaesthesia [10]. However, only means of blocks of reaction time trials were reported, and it was not possible to compare our data directly.…”
Section: Discussionsupporting
confidence: 89%
“…This test is very sensitive to acute hypoglycemia, showing deterioration in performance at plasma glucose levels of ~3 mmol/1 (10,(40)(41)(42)(43), which compares favorably with other cognitive tests (43)(44)(45)(46)(47). It is thus a good marker of cognitive function (48) and, in particular, measures a function that is likely to be relevant to the performance of complex tasks such as driving (21,22). It is important to recognize that four-choice reaction time is not (nor is it intended as) an estimate of global cognitive function.…”
Section: Korzon-burakowsha and Associatesmentioning
confidence: 94%
“…We therefore studied counterregulatory hormone responses, symptoms, and fourchoice reaction time (as a marker of cognitive function [21,22]) during controlled experimental hypoglycemia in a group of seven poorly controlled type 2 patients, before and after improving glycemic control with insulin treatment, using a stepped hypoglycemic clamp protocol to allow determination of the plasma glucose thresholds at which these responses begin.…”
mentioning
confidence: 99%
“…Subjects then trained on the apparatus for measuring four-choice reaction time (21,22). In this test, the subject is presented with a computer screen divided into four quadrants.…”
Section: Research Design Andmentioning
confidence: 99%